2008
DOI: 10.1007/s10529-008-9672-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced tolerance to drought stress in transgenic tobacco plants overexpressing VTE1 for increased tocopherol production from Arabidopsis thaliana

Abstract: Tocopherol cyclase (VTE1, encoded by VTE1 gene) catalyzes the penultimate step of tocopherol synthesis. Transgenic tobacco plants overexpressing VTE1 from Arabidopsis were exposed to drought conditions during which transgenic lines had decreased lipid peroxidation, electrolyte leakage and H(2)O(2) content, but had increased chlorophyll compared with the wild type. Thus VTE1 can be used to increase vitamin E content of plants and also to enhance tolerance to environmental stresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
62
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(71 citation statements)
references
References 16 publications
7
62
0
2
Order By: Relevance
“…LsTC was clustered with TC from Helianthus annuus, since they both belonged to Compositae species. An earlier study has shown that TC could endow plants with enhanced tolerance to drought stress, along with higher tocopherol content and lower lipid peroxidation levels (Liu et al, 2008). There is enough evidence that tocopherol content correlates positively with tolerance to lo� temperature, �ater �eficit or salt stress in �ifferent plants (Yama�uchi��hinozaki and Shinozaki, 1994;Munne-Bosch et al, 1999;Guo et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…LsTC was clustered with TC from Helianthus annuus, since they both belonged to Compositae species. An earlier study has shown that TC could endow plants with enhanced tolerance to drought stress, along with higher tocopherol content and lower lipid peroxidation levels (Liu et al, 2008). There is enough evidence that tocopherol content correlates positively with tolerance to lo� temperature, �ater �eficit or salt stress in �ifferent plants (Yama�uchi��hinozaki and Shinozaki, 1994;Munne-Bosch et al, 1999;Guo et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The change in cell membrane permeability and the degree of cell destruction caused by the stresses can be reflected directly through the change in electrolyte permeability, which was measured by the rate of relative electrolyte leakage (82). Moreover, enhanced tocopherol accumulation also occurs in response to a variety of abiotic stresses including high light, drought, high salinity, and cold and may provide an additional line of protection from oxidative damage (38,(83)(84)(85). In this study, leaves from the freeze-stressed BSMV PAP6-liketreated plants had distinctly more severe droop and wilt than the freeze-stressed viral controls.…”
Section: Identification Of Winter-responsive Proteins In Bread Wheatmentioning
confidence: 99%
“…In addition, Guo et al (2008) found that Triticum aestivum ubiquitin 2 (Ta-Ub2) accelerated the germination of seedlings under water deficit conditions and then improved the CO 2 assimilation rate of transgenic plants under both drought and non-drought conditions [8] Furthermore, a 3.8-fold higher level of ascorbate peroxidase (APX5) activity enhanced the net photosynthetic rate, and reduced toxicity of H 2 O 2 in transgenic tobacco plants [9]. However, tocopherol cyclase (VTE1) decreased lipid peroxidation, electrolyte leakage and H 2 O 2 content, and increased chlorophyll and tocopherol content in transgenic tobacco as compared to wild type plants in response to drought stress [10]. In addition, the LTP gene family, which includes at least five tightly regulated and differentially expressed genes, was linked to increased accumulation of cuticular wax in leaves of tree tobacco in response to periodic drought [11].…”
Section: Introductionmentioning
confidence: 99%